The effect of lyophilized platelet rich plasma in a third molar extraction socket and its surrounding tissues / Jonathan Rengarajoo - Jonathan, Rengarajoo (2019)
Lyophilized platelet rich plasma (LPRP) is centrifuged platelet cells that have been freeze dried into powder form, available for reconstitution for use at any point of time. a granules in platelets contain mitogenic, chemotactic growth factors and associated healing molecules. Since the socket healing is dynamic in nature, this study tried to determine if repeated placement of LPRP helps in the healing process of the associated soft and hard tissue. Methods: Commercially prepared LPRP was randomized to be placed/injected into fresh sockets using a third molar surgical model. The control contralateral sockets of the same patient did not receive anything. The application was done intraoperatively, at 1 month and 2 months postoperatively. The endpoints measurement was post-operative pain, swelling, trismus, pocket depth at mid distal adjacent second molar and bone formation in extraction socket; the last was assessed radiographically. Results: Fifteen healthy young adults were recruited into this study. They received standard bilateral wisdom tooth surgery under general anaesthesia, with the LPRP prepared commercially at least 1 month ahead. There was no significant difference in post-operative pain, size of swelling, trismus and bony healing within their specific timeline of study. There was no early significant difference with regards to pocket depth at mid distal second molar, however, the LPRP group showed significant reduction in pocket depth at 2 months postoperative. Conclusion: LPRP seems to improve soft tissue healing at the adjacent tooth, suggesting that the application of LPRP may be beneficial to periodontal health.